2014
DOI: 10.1523/jneurosci.1846-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mGlu5 Receptor-Dependent Synaptic Plasticity and Coupling to Homer Proteins in the Hippocampus of Ube3A Hemizygous Mice Modeling Angelman Syndrome

Abstract: Angelman syndrome (AS) is caused by the loss of Ube3A, an ubiquitin ligase that commits specific proteins to proteasomal degradation. How this defect causes autism and other pathological phenotypes associated with AS is unknown. Long-term depression (LTD) of excitatory synaptic transmission mediated by type 5 metabotropic glutamate (mGlu5) receptors was enhanced in hippocampal slices of Ube3A mϪ/pϩ mice, which model AS. No changes were found in NMDA-dependent LTD induced by low-frequency stimulation. mGlu5 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 60 publications
(10 reference statements)
3
55
0
Order By: Relevance
“…We conclude that physiologically fluctuating levels of glutamate might be unable to modify the interaction between mGluR5 and intracellular signaling mediators in a pathophysiological A␤o-dependent disease state. Similar pathophysiological association states between mGluRs and Homer scaffolding proteins have been proposed in the context of several neurological diseases, including fragile X syndrome and Angelman syndrome (48,49). Our data suggests that preventing A␤o-induced activation of the PrP C -mGluR5 signaling complex has potential clinical implications for Alzheimer disease.…”
Section: Figure 7 Fyn Kinase Inhibition Prevents Activation Of Pyk2 supporting
confidence: 82%
“…We conclude that physiologically fluctuating levels of glutamate might be unable to modify the interaction between mGluR5 and intracellular signaling mediators in a pathophysiological A␤o-dependent disease state. Similar pathophysiological association states between mGluRs and Homer scaffolding proteins have been proposed in the context of several neurological diseases, including fragile X syndrome and Angelman syndrome (48,49). Our data suggests that preventing A␤o-induced activation of the PrP C -mGluR5 signaling complex has potential clinical implications for Alzheimer disease.…”
Section: Figure 7 Fyn Kinase Inhibition Prevents Activation Of Pyk2 supporting
confidence: 82%
“…This probably occurs as a consequence of the fact that DHPG-induced LTD in the Schaffer collateral/CA1 synapse is induced by activation of postsynaptic mGluR5 receptors but has been shown also by others to be associated with an increase of paired pulse ratio, indicating a decrease in transmitter release probability during long-term depression (41). Accordingly, we observed an increase of PPR in wild-type mice after DHPG during LTD expression but not in knock-out mice after DHPG application.…”
Section: Discussionmentioning
confidence: 83%
“…However, there is limited evidence to suggest that ␤-arrestins interact with mGluRs to regulate either their endocytosis or signaling, with the majority of studies suggesting that ␤-arrestins play no role in regulating the activity of mGluRs (28). Nevertheless, spinophilin has been demonstrated to bind directly to GRK2 and G␤5, and GRK2 plays a central role in regulating Group I mGluR desensitization and internalization (34,41). Thus, it is possible that spinophilin interactions with Group I mGluRs may regulate GRK2 interactions with Group I mGluRs, thereby contributing to the regulation of their endocytosis and signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired hippocampal neurogenesis could conceivably compromise hippocampal function and amplify cognitive defect seen in AS mice. So far, several contributing factor have been identified that could lead to learning and memory impairment in AS mice, which includes aberrant activity of hippocampal CAMKIIa [13,14], enhanced neuregulin-Erb4 signalling [33], defect in experience-dependent synaptic plasticity [34,35] etc.…”
Section: Discussionmentioning
confidence: 99%